2007
DOI: 10.1007/s10561-007-9040-5
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of heart valve and arterial allografts in the European Homograft Bank (EHB): comparison of two different antibiotic cocktails in low temperature conditions

Abstract: The aim of the study was to compare the efficiency of two different antibiotic cocktails in the cardiovascular allograft decontamination. Low temperature, low-concentration antibiotic cocktail with Cefoxitin, Lincomycin, Polymixin B and Vancomycin was decontamination protocol in EHB for many years. The modified cocktail doesn't contain Cefoxitin. The study had two steps. First step: cardiovascular allografts from 80 donors are incubated in classical (group 1) or modified cocktail (group 2). Second step: 184 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
4
34
1
Order By: Relevance
“…The proceeded heart valve and artery tissues are incubated in the antibiotic cocktail at the temperature of 4°C for between 20 and 48 h not exceeding 72 h. The preliminary results have revealed that this 3-antibiotics' cocktail achieved a decontamination rate equivalent to that of the former 4-antibiotics' cocktail (Jashari et al 2007). However, the study group of this previous report is rather small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proceeded heart valve and artery tissues are incubated in the antibiotic cocktail at the temperature of 4°C for between 20 and 48 h not exceeding 72 h. The preliminary results have revealed that this 3-antibiotics' cocktail achieved a decontamination rate equivalent to that of the former 4-antibiotics' cocktail (Jashari et al 2007). However, the study group of this previous report is rather small.…”
Section: Introductionmentioning
confidence: 99%
“…Although the setting of antibiotic treatment does have a significant impact on decontamination success, to date, no consensus exists on an optimal formula. Several different decontamination protocols are applied in the different tissue banks (Angell et al 1976;Strickett et al 1983;Kirklin et al 1987; BarrattBoyes et al 1987;Gall et al 1995;Stolinski et al 2006;Jashari et al 2007). The differences between these protocols are mainly in the composition and concentration of antibiotic cocktail, the temperature and the duration of antibiotic incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the retrieval of the allograft source material from the NHBDs was envisaged as one of the possibilities for increasing the yield of cardiovascular allografts. Consequently, some of the procured cardiovascular tissues arriving in the Tissue Establishments are primarily contaminated [8]. Earlier methods used for allograft decontamination were harmful for allograft integrity [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Different Tissue Establishments worldwide, responsible for cardiovascular allograft decontamination, have adopted different cocktails of antibiotics, under different temperature conditions and for varying duration [4][5][6]. Since the cell viability preservation of the heart valves signifies the valve quality preservation [7], many antibiotics such as antimycotic drugs [8] were removed from some decontamination protocols. Some long-term studies on implanted allografts have shown that allograft viability is a prerequisite for graft survival [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation